Aspects of water quality and basic sanitation in a rural settlement in the state of São Paulo: diagnosis and perspectives for the improvement of the socio-environmental quality (Research, Society and Development, 2021)
The provision of potable water is needed in rural settlements and determines health and income in such populations. However, rural settlements have been established in Brazil without the needed structures to guarantee quality water and proper residues disposal, which may negatively impact these communities. The aim of this study was to investigate some of these aspects in the rural settlement “União da Vitória”, in the municipality of Suzanápolis/SP. Structured interviews assessing the community environmental perception on water quality and basic sanitation were performed, as well as the determination of faecal coliforms in the water consumed by the population was done. The majority of the population lives in the settlement since its foundation in 2005 and work exclusively in their land as farmers but have deficient information regarding basic sanitation. Out of the 50 sampled farms, 9% consumed water contaminated with faecal coliforms, all found in shallow water wells, which are more vulnerable to contamination than deeper water wells. This percentage is far lower than in other rural settlements found throughout Brazil. These data point out to the need to inform this population about adequate methods for the construction of water and sewage wells and outline the necessity of this population to be assisted by public and private sanitation entities in Brazil.